(untitled) (JURNAL ADMINISTRASI PUBLIK, 2019)
Service and satisfaction are two things that cannot be separated, because with satisfaction, the relevant parties can correct each other until the services provided are better or worse. It is very influenced by every officer in providing services, in other words, services that can be satisfying are services carried out based on applicable provisions and can understand what is being asked by the community from the department of service itself. Patient satisfaction is a major challenge in the provision of health services today. In general, plenary health services are health services that include promotive (health improvement), preventive (prevention), curative (treatment), and rehabilitative (recovery). (Law No. 44 of 2009 concerning Hospitals). In Law No. 25 of 2009 concerning public services, in Article 18 it is explained that the community has the right to obtain quality services in accordance with the principles and objectives of the service. Keywords: Satisfaction, Service, and Hospitalization